Study to determine self-medication pattern and drug use behavior in rural areas of Etawah district - Singh, Nishant; Sahu, Priyanka; Saroj, Mahendra Kumar; Singh, Vaibhav; Siddiqui, Arshiya Masood (International Journal Of Community Medicine And Public Health, 2022)
Background: According to William Osler, a great feature which distinguishes man from animals is the desire to take medicine. Self-medication is an age-old practice. According to world health organization guidelines “Self-medication is defined as use of medicinal products by the individuals to treat self-recognized disorders or symptoms, or the intermittent or continuous use of a medication prescribed by a physician for chronic or recurring diseases or symptoms Methods: The study population included study subjects from the rural areas of Etawah district. A total sample of 200 was recruited in the study based on 40×5 cluster sampling technique Results: most of the participants in rural areas 65% belong to the age group 20-39 years. Among the rural participants males were 134/200 (67.0%) and females were 66 (33%). Most of the participants in rural areas were married i.e. 76.0%. Most of the participants (50%) belonged to joint family followed by nuclear family (40%) in rural areas. Most common reason for self-medication practice in rural area most common reason for practice of self-medication was high fee which makes 29% (58) of all respondent and other reasons were Doctor/clinic away from home (27.5%), to save time (20.5%), medicine of family member (6%), no trust in doctor (0.5%) and pharmacist advice (3.5%). Conclusions: Most common age group indulged in the practice of self-medication was 20-39 year in rural study area.